PENINGKATAN HASIL BELAJAR PESERTA DIDIK DENGAN Model PjBL (PROJECT BASED LEARNING) PADA PEMBELAJARAN MATEMATIKA KELAS XI DI SMA N 14 SEMARANG (psnppg, 2024)
This research aims to improve students' mathematics learning outcomes on Rank and Root Form material. This type of research is a Class Action Research carried out at SMA Negeri 14 Semarang in the odd semester of the 2023/2004 school year through the Project Based Learning method. This class action research is carried out in two cycles. The subject of the study is students of class XI-3 SMA Negeri 14 Semarang. The research instruments used are learning tools, evaluation/reflection sheets, and observation sheets. The data collection technique in this study is by observation in the form of observation sheets and tests in the form of questions given to students at the end of each cycle to find out the learning outcomes of students. In this study, the Quantitative Descriptive Analysis technique was used. Based on data analysis, the results were obtained that by using  the Project Based Learning  model on rank and root form materials, there was an increase in learning outcomes, namely pre-cycle by 41.18%, cycle I by 64.71%, and cycle II by 82.35%. It can be concluded that the application of the PjBL (Project Based Learning) model to the Correlation Coefficient and Determination Coefficient materials improves student learning outcomes.
Keywords: Pembelajaran Matematika; Project Based Learning; Hasil Belajar